Revenue-Generating Schemes for International Unions - Boiar, Andrii O.; Бояр, Андрій Олексійович (Center for Economic Integration, Sejong Institution, Sejong University, 2014)
This paper investigates possible options for generating revenue in international unions. The empirical evidence is found for three types of revenue-generating schemes: contributions, direct taxes, and the combination of two. Discussion of peculiarities, advantages and shortcomings of each scheme led to the conclusion that financial needs, interstate heterogeneity, objectives and success of integration are the key factors determining the choice of a revenue-generating scheme. There is no clear pattern in the distribution of the schemes among different international unions. However, mixed scheme becomes more preferable to ensure sustainable financing international unions. Also, direct tax scheme would be the infant stage of a tax union that had no precedent in the modern history of economic integration.
Keywords: Revenue; Tax; International Union; Budget; Contribution